The Gender Order in Sumak Kawsay and Suma Qamaña. A Look at the Current Debates in Bolivia and Ecuador - Silvia Vega Ugalde (Íconos, 2014)
Sumak kawsay and suma qamaña are concepts proposed by the original peoples in Andean countries that have been adopted in the Bolivian and Ecuadorian constitutions to denote a new economic and political model for society and state, and a new vision with respect to nature. In this article I consider what this concept offers for questioning predominant gender relations. To respond, I enquire into the positions that the representatives of the indigenous peoples, of state organisms, and of feminist organizations adopt in both countries. The article demonstrates the different reach of the debate in Ecuador and Bolivia and touches upon the policy of de-patriarchalization installed in the latter that has dynamized political discussions in recent years.